An Investigation of Technological Pedagogical and Content Knowledge (TPACK) Competencies of Pre-Service Visual Arts Teachers - Kara, Sema (ISTES Organization, 2021)
This study aimed to examine TPACK (Technology, Pedagogy and Content Knowledge) competencies of pre-service visual arts teachers. Based on the descriptive and comparative survey model, TPACK competencies of pre-service visual arts teachers were compared on variables of gender, year of study and academic achievement. The participants of the study were 253 pre-service teachers studying in department of visual arts in Education Faculties of Atatürk, Karadeniz Teknik, Mersin and Necmettin Erbakan Universities. TPACK Competencies Scale was used to collect research data. The findings showed that TPACK competencies of pre-service visual arts teachers were low in terms of technology knowledge, but high in content knowledge. In addition, their TPACK competencies vary based on gender, year of study and academic achievement.
Keywords: 4. Education